Attitude and conduct towards the fourth dose of the COVID-19 vaccine in health personnel in the Lambayeque Region - 2022 - Pecsén-Monteza, José (2023)
Introduction: Twelve doctors and seven nurses died in the Lambayeque Region due to COVID-19, even so, a refusal to be vaccinated with the fourth dose is observed. Objective: To determine the attitude and behavior towards the fourth dose of vaccine against COVID-19 in Lambayeque health personnel. Materials and methods: Descriptive and cross-sectional study, in 371 health workers, selected through non-probabilistic snowball sampling, we shared the virtual survey on attitude and behavior with responses on the continuous Likert scale "agree". Results: average age 40 years, 53.4% ​​worked in EsSalud, 43.1% were doctors, 27.7% with comorbidities, highlighting Arterial Hypertension, Obesity and Diabetes Mellitus. 74% refused to be vaccinated. 51.8% have a neutral attitude and 48.3% unstable conduct against vaccination. Conclusions: The attitude and behavior towards vaccination is neutral and unstable respectively, it is associated with sex and has a low effective vaccination rate.